The Effect of Cooperative Learning Model of Structured Numbered Head (SNH) on The Learning Outcomes of Islamic Religious Education - Amirudin Amirudin (Nazhruna: Jurnal Pendidikan Islam, 2022)
This research is based on students' habits if given group assignments always rely on other friends. To overcome this, it is necessary to apply a cooperative learning model of the numbered head type structure (structured numbered head), the method used is a descriptive quantitative method using correlation studies with cause and effect study. The population is 355 students (all grade VII students). While sampel 20% or as many as 72 students. Data is collected using questionnaires. Statistical analysis measures use partial tests, normality tests, correlation tests, hypothesis tests and influence tests. The calculation of variable X and variable Y obtained a value of 59.11 and a value of 1.99. Then it can be concluded that >, meaning that the hypothesis that the author proposed is accepted. This means that there is a positive or significant influence between the Structured Numbered Heads (SNH) Type Cooperative Learning Model on the Learning Outcomes of Students of Islamic Religious Education Subjects Class VII SMP Negeri 5 Karawang Karawang Regency. While the calculation of the correlation coefficient of 0.99 can be categorized as a perfect correlation because it is between 0.81 - 1.00. There is a degree of correlation or influence of variable X on variable Y of 0.14. So obtaining the influence of variable X on variable Y by 86% means that there are 14% other factors that can affect the Learning Outcomes of Students of Islamic Religious Education Subjects Class VII SMP Negeri 5 Karawang Karawang Regency.